2021
DOI: 10.21037/atm-21-5081
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-assisted detection and classification of colorectal polyps under colonoscopy: a systematic review and meta-analysis

Abstract: Background: Artificial intelligence (AI) is used to solve the problem of missed diagnosis of polyps in colonoscopy, which has been proved to improve the detection rate of adenomas. The aim of this review was to evaluate the diagnostic performance of AI-assisted detection and classification of polyps in colonoscopy. Methods:The literature search was undertaken on 4 electronic databases (PubMed, Web of Science, Embase, and Cochrane Library). The inclusion criteria were as follows: studies reporting AI-assisted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Recently, research and development of AI for the detection and diagnosis of colorectal tumors have been actively conducted and are commercially available in some countries [16][17][18][19][20][21][22]. Approximately a quarter of the respondents replied that it is used based on necessity in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research and development of AI for the detection and diagnosis of colorectal tumors have been actively conducted and are commercially available in some countries [16][17][18][19][20][21][22]. Approximately a quarter of the respondents replied that it is used based on necessity in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…analysis of these studies was recently published [10]. They reported that the ADR associated with CADe had 95% sensitivity and good discrimination ability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, the usefulness of artificial intelligence (AI) has been reported in solving complex multinomial problems in various fields, including computer-aided detection (CADe) in medicine. Large prospective trials have been conducted on colonoscopy AI, and a meta-analysis of these studies was recently published 10 . The authors reported that the ADR associated with CADe had 95% sensitivity and good discrimination ability 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In order to address this issue and reduce EDMR, computer-aided diagnostic methods employing artificial intelligence algorithms have increasingly been used for improving the detection and characterization of cancer polyps. [9][10][11][12][13][14][15][16][17][18] Algorithms such as Support Vector Machines (SVMs), k-nearest neighbors (kNNs), ensemble methods and random forests, [9][10][11][12] and convolutional neural networks (CNNs) with various architectures such as Residual networks (ResNet), Densely connected CNNs (DenseNet), and AlexNet, [13][14][15][16][17][18] have shown promising results in this field. However, most such machine learning (ML) algorithms have limitations, most notably that they tend to perform poorly on smaller and unbalanced datasets, leading to overfitting, biases, and under-coverage of less represented classes.…”
Section: Introductionmentioning
confidence: 99%